2021
DOI: 10.1088/1741-4326/ac2523
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication routes for advanced first wall design alternatives

Abstract: In future nuclear fusion reactors, plasma facing components have to sustain specific neutron damage. While the majority of irradiation data provides a relatively clear picture of the displacement damage, the effect of helium transmutation is not yet explored in detail. Nevertheless, available results from simulation experiments indicate that 9%-chromium steels will reach their operating limit as soon as the growing helium bubbles extent a critical size. At that point, the material would most probably fail due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Since such imperfections might have to be tolerated in an industrial production, we continued the mockup fabrication and used this as a robustness test. More details are given in [37]. The bonding surface of the EUROFER plate was also milled over (by about 0.1 mm) to remove the oxide layer and to ensure a proper diffusion weld process.…”
Section: Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since such imperfections might have to be tolerated in an industrial production, we continued the mockup fabrication and used this as a robustness test. More details are given in [37]. The bonding surface of the EUROFER plate was also milled over (by about 0.1 mm) to remove the oxide layer and to ensure a proper diffusion weld process.…”
Section: Fabricationmentioning
confidence: 99%
“…In summary, the mockup fabrication was performed using solely industrial-based or commercially established processes, which could also be applied to the production of the real components-the breeding blankets. More information on the industrial scale production of the used ODS steel can be found in [37]. The fabrication included two weak points that would allow for assessing the robustness of the design in terms of (1) small imperfections in machining and handling a 2 m 2 size surface of a massive component in the several tons range within an industrial environment and (2) possible crack initiation domains due to fabrication, material, operational, or processing shortcomings.…”
Section: Fabricationmentioning
confidence: 99%
“…On the other hand, the candidate materials typically selected for the structural components of a fusion power plant all have isotropic cubic crystal structure. It is either the bodycentred cubic structure characterising iron-chromium alloys, ferritic steels and tungsten, or the face-centred cubic structure of copper, copper alloys and austenitic steels [2,[14][15][16][17]. Exposure of these materials to irradiation gives rise to swelling or, in other words, to the predominantly isotropic volume expansion resulting from the accumulation of defects in the material [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the candidate materials typically selected for the structural components of a fusion power plant all have isotropic cubic crystal structure. It is either the body-centred cubic (bcc) structure characterising iron-chromium alloys, ferritic steels and tungsten, or the face-centred cubic (fcc) structure of copper, copper alloys and austenitic steels [2,[14][15][16][17]. Exposure of these materials to irradiation gives rise to swelling or, in other words, to the predominantly isotropic volume expansion resulting from the accumulation of defects in the material [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%